CountApPH an application for human-assisted tallying of scanned ballot images from ballot templates used in 2013 Philippine automated elections - Ocfemia, Danen Clint P. (2016)
This research project describes the design and implementation of an application that automatically tallies vote markings in scanned ballot images from ballot templates used in the 2013 Philippine national election. The application can help in conducting risk-limiting election audits to verify election results.